Analysis of Institutional Capacity-Building Barriers in Urban Governance: A Strategic Approach in Tehran Metropolis - Reza Shadmanfar, Amirhosein Pourjohari, Hosein Imani Jajarmi (The International Journal of Multiphysics, 2025)
Introduction: Institutional capacity-building in neighborhood communities is a critical strategy for urban sustainable development. This study aims to analyze the challenges and implications of institutional capacity-building in Tehran’s neighborhood communities. Materials and Methods: This qualitative study employed conventional content analysis. The research sample consisted of 22 urban experts selected through purposive sampling. Data were collected via semi-structured interviews and analyzed using the Graneheim and Landman method with MAXQDA 2018 software. Findings: The results revealed the multidimensional implications of institutional capacity-building in Tehran’s neighborhood communities. Content analysis identified six key subcategories emerging from the interactions of individual, social, and institutional factors. At the individual level, participants emphasized personal capability enhancement and social skill development. Collective-level findings highlighted the importance of strengthening social capital and neighborhood solidarity. Conclusion: The study demonstrates that institutional capacity-building is a strategic approach to urban sustainable development. The primary challenges include structural limitations, a lack of specialized human resources, and cultural barriers. Success requires a comprehensive, participatory approach to address the ongoing urban changes. The key outcome is the identification of the necessity for continuous institutional restructuring to empower local communities.